Water Ice in AGN and Starbursts - Yeghikyan, A. G.; Samsonyan, A. L.
Complex chemical species are easier formed in a solid phase, for example in a mixture of ices of water, carbon oxides, methane, ammonia, methanole and other, less abundant molecules. Ultraviolet photons in the range 5 - 13.6 eV and the charged particles with MeV-GeV energies serve as an energy source of reactions. Icy particles containing mentioned substances, can exist only in internal areas of the interstellar molecular clouds protected from in uence of external ultraviolet radiation. However cosmic rays are capable to penetrate in clouds and to cause an irradiation of ices by means of secondary ultra-violet photons necessary for initiation of chemical reactions of complexisation. In this work a survivability of ices under harsh conditions of active galaxies is discussed. Preliminary model calculations show that abundances of ices depend not only on ionization parameters of the clouds but also on the shape of incident radiation that is on presence and level of hard ultraviolet and X-ray radiation. The last circumstance is directly related to the radiation of the accretion disk of galaxies with active nuclei and can be used to classify active galaxies, for example to distinguish starburst galaxies from those with active nuclei.
Keywords: Astronomy